Determining the effects of L-tryptophan addition to diets containing 30% dried distillers grains with solubles on finishing pig growth performance - S Nitikanchana; J Usry; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 845 pigs (PIC 380 × Mosanto; initially 163 lb) were used in a 61-d study to determine the effects of L-tryptophan addition to diets containing 30% dried distillers grains with solubles (DDGS) on the growth performance of finishing pigs reared in a commercial environment. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 5 dietary treatments in a completely randomized design with 25 to 30 pigs per pen and 6 replications per treatment. Treatments included 4 standardized ileal digestible (SID) tryptophan:lysine ratios (15, 17, 19, and 21% of lysine) using crystal- line L-tryptophan added to the 15% diet. An additional diet used soybean meal as a source of tryptophan to provide a SID tryptophan:lysine ratio of 21%. Overall (d 0 to d 61), increasing the SID tryptophan:lysine ratio did not affect (P>0.25) growth performance. Pigs fed a diet containing a 21% SID tryptophan:lysine ratio with added soybean meal as the tryptophan source had (P = 0.01) poorer F/G compared with pigs fed the diet with a 21% SID tryptophan:lysine ratio from crystalline tryp- tophan. Although not significant, pigs fed the 21% SID tryptophan:lysine ratio with soybean meal as the tryptophan source had a 3% reduction in ADG compared with those fed a SID tryptophan:lysine ratio of 21% using L-tryptophan. Otherwise, ADG and ADFI (P = 0.37, P = 0.82) were similar across all treatments. In conclusion, increasing the SID tryptophan:lysine ratio from 15 to 21% by adding crystalline tryptophan (L-tryptophan) did not influence finishing pig growth performance.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; SID tryptophan:lysine ratio; Tryptophan; DDGS; Growth; Finishing pig